Synthesis and investigation of anti-tyrosinase and antioxidant activity of new halogenated xanthone derivatives - Baharuddin, Fatin Farhana (2023)
Excess melanin production in skin cells promotes dermatological diseases such as hyperpigmentation, ageing, and other skin-related diseases. Tyrosinase enzyme catalyses the oxidation of L-tyrosine substrate to melanin, via formation of L-3,4- dihydroxyphenylalanine (L-DOPA). Thus, tyrosinase inhibitors can lower melanin production to achieve whitening effect on the skin. Whitening products such as hydroquinone and kojic acid that are commonly used nowadays, might be harmful to human skin. This research aimed to produce 20 non-toxic halogenated tyrosinase inhibitors synthetically using Grover-Shah and Shah (GSS) method and determine their tyrosinase inhibitory activity using tyrosinase mushroom Agaricus bisporus assay with kojic acid as positive control. Six compounds were found to inhibit the enzyme with inhibition percentage of more than 50%. Among these six active compounds, three compounds (15, 16 and 17) showed high potency. Their half-maximal inhibitory concentration (IC50), enzyme kinetic analysis and antioxidant properties were determined. The IC50 values for compounds 15 (7.8 μg/ml, 75 μg/ml), 16 (9 μg/ml, 118 μg/ml) and 17 (10 μg/ml, 100 μg/ml) in L-tyrosine and L-DOPA substrates respectively, demonstrate their strong action in comparison to kojic acid as control (IC50 4 μg/ml, 7.8 μg/ml). Enzyme kinetic analysis demonstrated that compounds 15 and 17 as uncompetitive inhibitor and compound 16 as mixed type inhibitor respectively. In antioxidant assays, only compound 16 exhibited a high antioxidant activity (IC50 18 μg/ml) in DPPH assay and 2.93 mM/g in FRAP assay with ascorbic acid and quercetin as positive controls. Additionally, compound 16 revealed an IC50 value of 43.33 μM against the in vitro HaCaT skin cell line, indicating a weak toxicity on human skin cells. Compound 16 also revealed a non-toxic property for screening of toxicity test when tested against the in vitro brine shrimp toxicity assay at a dose of 1000 μg/ml. From the in vivo zebrafish embryo toxicity assay, results have shown that compound 16 was having a non-toxic property based on the parameters such as hatching rate, survival rate, heartbeat rate and obtained a LC50 value of 197.2 μg/mL. Furthermore, the molecular docking analysis showed their binding interactions between mushroom tyrosinase protein structure (PDB ID: 2Y9X) for compound 16 with a binding affinity of (-7.7 kcal/mol) and the compounds as the ligands through in silico approach. These data suggest that potent halogenated xanthone derivatives have the potential to be developed as new candidates for skin whitening agents with antioxidant and non-toxic properties in cosmetic industries and for pigmentationrelated diseases.